Fatty acid composition of rice lipids by gas-liquid chromatography - Lugay, J.C.; Juliano, Bienvenido O. (Wiley, 1964)
Gas‐liquid Chromatographic analysis of the methyl ester of lipids of four rice varieties showed that bran lipids had significantly higher mean contents of linoleic and linolenic acids, but lower contents of myristic, palmitic, palmitoleic, and stearic acids than milled rice lipids. Nine fatty acids were detected. The principal components were oleic, linoleic, and palmitic, which also was confirmed by thin‐layer chromatography of the esters.